A rare canonical splice-site variant in VPS13B causes attenuated Cohen syndrome. (2nd January 2022) - Daich Varela, Malena; Motta, Fabiana Louise; Webster, Andrew R.; Arno, Gavin
ABSTRACT: Background: To describe a patient with a history of obesity, retinal dystrophy, type II diabetes, and mild cognitive impairment; found to harbour biallelic splice-site variants in VPS13B . Materials & methods: A complete ophthalmic evaluation was performed at Moorfields Eye Hospital (London, United Kingdom), consisting of measurement of best-corrected visual acuity (BCVA), slit lamp and dilated fundus evaluation, colour, autofluorescence and near-infrared retinal imaging, spectral domain-optical coherence tomography, and electroretinogram (ERG). Whole-genome sequencing was performed as part of the UK's 100, 000 Genomes Project. Results: A 26-year-old Pakistani man with normal appearance, stature, and head size presented with decreased BCVA and severely constricted visual fields to our Ophthalmic Genetics clinic. He had a history of obesity, type II diabetes, and mild cognitive impairment. His evaluation showed retina-wide, severe photoreceptor dysfunction in both eyes, with undetectable scotopic and photopic ERG waveforms. Genomic analysis identified a homozygous rare splice donor variant in the VPS13B gene (c.5024+2T>C) that was demonstrated to lead to skipping of the in-frame exon 31 (p.Gln1607_Ser1675delinsHis). Conclusions: Exon 31 skipping in VPS13B may lead to a hypomorphic change, with partial gene function and an incomplete, mild Cohen syndrome-like phenotype.